2016
DOI: 10.12693/aphyspola.129.200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of X-ray Irradiation on Articular Cartilage Mechanical Properties

Abstract: A load bearing tissue found at the ends of articulating bones, the articular cartilage provides low friction surfaces for efficient movement. Its mechanical properties are determined by the structure and composition of type II collagen, proteoglycans and interstitial fluid. This work investigates the effects of X-ray irradiation, previously shown to affect the biological properties of the articular tissue, on mechanical properties of articular cartilage using polarized light microscope for imaging and compress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…In instantaneous experiments however, although responses are similar to the control, it is evidently seen that increasing stress values match with lower strain curves. In a previous study on the effects of ROS resulted by x-ray radiation on equilibrium stiffness of cartilage matrix [6], experimental curves were found to be more similar to those of the control indicating higher deteriorating rate of direct effect of ROS on the mechanical properties of the articular cartilage.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In instantaneous experiments however, although responses are similar to the control, it is evidently seen that increasing stress values match with lower strain curves. In a previous study on the effects of ROS resulted by x-ray radiation on equilibrium stiffness of cartilage matrix [6], experimental curves were found to be more similar to those of the control indicating higher deteriorating rate of direct effect of ROS on the mechanical properties of the articular cartilage.…”
Section: Discussionmentioning
confidence: 82%
“…Initially, the force was applied and the cartilage was allowed to come to equilibrium. The cartilage surface was then displaced by 0.7 mm in total of ten steps; each step being 70 µm [6]. Stress was calculated as load per unit macroscopic sectional field.…”
Section: Compression Tests For Equilibrium Modulusmentioning
confidence: 99%
“…Attempts were made to keep the overall scanning time similar for all samples but differences in exposure time and number of projections may still have affected comparison between the scans. Previous studies have shown that ionizing radiation can have a significant effect on a range of measured properties in articular cartilage samples 43,44 , including its mechanical properties 45 ; bone is also negatively affected 46 . Low energy X-rays interact with these low-density materials and cause more damage than high energy beams causing particular problems for the low voltages used throughout this study 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Six control samples, seven samples exposed to 3.33-GBq technetium-99m, and nine samples exposed to 2.035-GBq technetium-99m sestamibi were analysed. The details related to the compression method can be found in the previous study [15].…”
Section: Compression Tests For Equilibrium Modulusmentioning
confidence: 99%